The Syndrome of Neurocognitive Impairment and Pain Management in Neurointensive Care Patients - Omar A. Ayoub, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Sedatives and analgesics are commonly used and warranted in the majority of ICU patients. Neurocritical patients present a particular challenge in these dimensions of critical care since their assessments are marred by confounders, staff goals of maintaining comfort, and the need for cooperative awake patient for neurological assessments. In the literature, there is a dearth of information on the topic of analgesia, sedation and delirium among the neurocritically ill patients. No objective instrument has been validated in this population. Outcomes and responses to pharmacologic treatment are not reported, and recommendations as to management can only be considered based on expert opinion. Much needs to be done in this vulnerable patient population to a better guide care. This review elaborates on the current knowledge on the issues of delirium as well as the current practice in managing pain, and sedation in neurocritically ill patients.